Multimodal texts in support of linguistic and critical thinking development in English for specific purposes - Hadjiconstantinou, Stavroulla (My University, 2021)
In light of widespread recognition of the need to explore new forms of literacy brought by the contemporary semiotic world, this study explores the potential Critical Thinking (CT) may offer in developing learners’ critical literacy in an English for Specific Purposes (ESP) context enhanced with the use of technology. Drawing on research in critical pedagogy that highlights the importance of raising learners’ critical awareness through language, I explore how critical practices of identifying and negotiating the expression of personal opinion in multimodal texts, in an English for the Media context particularly sensitive to issues of criticality, can enhance the development of multimodal literacy. This development is informed by Design-Based Research (DBR) (McKenney & Reeves, 2013), in which iteration and refinement of an intervention designed around these practices leads to the development of principles deriving from the evolution of the design.
Keywords: critical pedagogy; ESP; multimodal literacy